ANALISIS ERGONOMI PADA PEMBELAJARAN DARING MENGGUNAKAN SMARTPHONE DI MASA PANDEMI COVID-19 - Umi Kulsum (Universitas Negeri Medan, 2022)
Abstract: Ergonomic Analysis of Online Learning Using Smartphones During the Covid-19 Pandemic. The aims of the study were: (1) to analyze ergonomically the behavior of students when participating in online learning, (2) to analyze physical muscle complaints (MSD) and psychological (stress and smartphone addiction). The subjects of this research are students of the Fashion Design skill program at SMK Negeri 5 Malang in the 2021/2022 academic year. The number of targets/respondents is 174 people. Data collection techniques were carried out by surveying students with a questionnaire. Using survey design method with cross sectional design. Measurement through PSS (Perceived Stress Scale) and SAS (Smartphone Addiction Scale) with a closed-ended question concept. The discussion in the study showed that of the 28 types of MSD complaints, complaints of severe pain in the right elbow (34%); back (24%); left shoulder (18%). Respondents included in the category of addicted to smartphones as much as 27%, and respondents suffering from stress, feeling anxious and depressed as much as 26%. Physical complaints are reduced by applying ergonomic considerations, namely by supporting the arm when using a smartphone.Keywords: smartphone, MSD, stress, ergonomic considerationsAbstrak: Analisis Ergonomi Pada Pembelajaran Daring Menggunakan Smartphone Di Masa Pandemi Covid-19. Tujuan penelitian adalah: (1) menganalisis secara ergonomi perilaku siswa saat mengikuti pembelajaran daring, (2) menganalisis keluhan fisik otot (MSD) serta psikis (stress dan smartphone addiction). Subjek penelitian ini siswa program keahlian Tata Busana SMK Negeri 5 Malang tahun ajaran 2021/2022. Jumlah sasaran/responden sebanyak 174 orang. Teknik pengumpulan data dilakukan dengan mensurvei siswa dengan angket. Menggunakan metode rancangan survei dengan cross sectional design. Pengukuran melalui PSS (Perceived Stress Scale) dan SAS (Smartphone Addiction Scale) dengan konsep closedended question. Pembahasan dalam penelitian menunjukkan dari 28 jenis keluhan MSD, keluhan sakit sekali pada siku kanan (34%); punggung (24%); bahu kiri (18%). Responden termasuk dalam kategori addicted to smartphone sebanyak 27%, dan responden menderita stress, merasa gelisah dan tertekan sebanyak 26%. Keluhan fisik dikurangi dengan menerapkan pertimbangan ergonomi, yaitu dengan menopang lengan saat menggunakan smartphone.Kata Kunci: smartphone, MSD, stress, pertimbangan ergonomi